2017
DOI: 10.1530/rep-16-0526
|View full text |Cite
|
Sign up to set email alerts
|

Luteal function during the estrous cycle in arginine-treated ewes fed different planes of nutrition

Abstract: Functions of corpus luteum (CL) are influenced by numerous factors including hormones, growth and angiogenic factors, nutritional plane and dietary supplements such as arginine (Arg), a semi-essential amino acid and precursor for proteins, polyamines and nitric oxide (NO). The aim of this study was to determine if Arg supplementation to ewes fed different planes of nutrition influences: (1) progesterone (P4) concentrations in serum and luteal tissue, (2) luteal vascularity, cell proliferation, endothelial NO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 116 publications
2
3
0
Order By: Relevance
“…Currently, the endocrine values for progesterone around the estrous are used in ewes to synchronize the estrus cycle (Maksimović et Gaviria & Hernández (1994) informed maximum mean values of progesterone on day 12 of the estrous cycle in crossbred ewes in Colombia of 15 nmol/L, which are higher than the observed values in this study on day 14 (mean 10.9 nmol/L). Progesterone levels normally drop on day 14 of the ovine estrous cycle (Bass et al 2017), which agrees with the present work. Balaro et al (2015) reported progesterone profiles of Santa Ines ewes in winter and summer under the tropical conditions of the state of Rio de Janeiro (Brazil) They found that about 50 % of the ewes had mean progesterone concentrations under 3.2 nmol/L, confirming the low reproductive seasonality in Santa Ines ewes.…”
Section: Resultssupporting
confidence: 93%
“…Currently, the endocrine values for progesterone around the estrous are used in ewes to synchronize the estrus cycle (Maksimović et Gaviria & Hernández (1994) informed maximum mean values of progesterone on day 12 of the estrous cycle in crossbred ewes in Colombia of 15 nmol/L, which are higher than the observed values in this study on day 14 (mean 10.9 nmol/L). Progesterone levels normally drop on day 14 of the ovine estrous cycle (Bass et al 2017), which agrees with the present work. Balaro et al (2015) reported progesterone profiles of Santa Ines ewes in winter and summer under the tropical conditions of the state of Rio de Janeiro (Brazil) They found that about 50 % of the ewes had mean progesterone concentrations under 3.2 nmol/L, confirming the low reproductive seasonality in Santa Ines ewes.…”
Section: Resultssupporting
confidence: 93%
“…Changes in gross and cellular morphometrics and serum concentration of metabolites and hormones in response to dietary treatments for this model have been reported previously ( Kaminski et al, 2015 ; Bass et al, 2017 ; Prezotto et al, 2020 ). Briefly, dietary treatments induced weight gain (9.6 ± 0.7 kg) in overfed ewes and weight loss (−13.9 ± 0.1 kg) in underfed ewes ( p ≤ 0.02).…”
Section: Resultssupporting
confidence: 75%
“…Animal care and dietary treatments were as previously described ( Kaminski et al, 2015 ; Bass et al, 2017 ). Briefly, a total of 48 Rambouillet-cross multiparous ewes (3–5 years of age and of similar genetic background) were housed individually (0.91 × 1.2 m pens) in a temperature-controlled room (14°C) with regulated light-dark cycle (12:12 h; lights on 0700 and off at 1900; initiated prior to the winter solstice).…”
Section: Methodsmentioning
confidence: 99%
“…While the results differed with Zeitoun et al, (19) who reported that injecting arginine pregnant ewes led to a decrease in growth hormone concentration during pregnancy. Bass et al, (23) confirmed that injecting arginine into mature ewes in anestrus phase resulted in a significant increase in growth hormone concentration within 15-30 minutes after injection .Refrences 1) Alawiy, I. K. M. and Al-Salmani, Th. R. M.…”
Section: -Growth Hormone Concentration (Table -5)mentioning
confidence: 85%
“…The results were similar with that of Yunta et al, (18) that giving arginine during pregnancy on the day 41 -146 which might be not stimulate the secretion of prolactin. Bass et al (23) confirmed that injecting arginine into mature, non-pregnant ewes significantly increased the concentration of prolactin. a. b. c. small letters within one row indicate significant differences between the treatments.…”
Section: -Concentration Of Prolactin (Table-4)mentioning
confidence: 90%